ogttMetrics: Data structures and algorithms for oral glucose tolerance tests [version 1; peer review: 1 approved with reservations] - Stubbs, Benjamin J; Frankston, Keith; Ramos, Marcel; Laranjo, Nancy; Sacks, Frank M; Carey, Vincent J (F1000 research, 2017)
We describe an open source software package, ogttMetrics, to compute diverse measures of glucose metabolism derived from oral glucose tolerance tests (OGTTs). Tools are provided to organize, visualize and compare OGTT data from large cohorts. Numerical difficulties in estimation of parameters of the Bergman minimal model are described, and in one large clinical trial, the simpler closed form index of Matsuda is observed to lead to similar rankings of individuals with respect to insulin sensitivity, and similar inferences concerning effects of modifications to carbohydrate content and glycemic index of experimental diets.